The Implementation of PQRST (Preview, Question, Read, State, Test) Method toImprove Activity and Learning Result of X1 Grade Students in SMA Negeri 1 Sawan in Academic Year 2012/2013. - Ayu Sukmawidiyanti, Ni Luh Ayu Sukmawidiyanti (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2013)
This study aims to: 1) improve students’ activity and learning by implementing PQRST method: 2) improve students’learning result by implementing PQRST method: 3) and describe students’ response to PQRST method. This research is a classroom action research study, which  subject in this research is X1 grade student of SMA Negeri 1 Sawan in academic year 2012/2013, and the objects of the research are learning activity, learning result and student’s response in comprehending  the uses of information technology and communication. Data for students’ learning activity was taken by using questionnaire, students’ learning result was taken by using test and students’ response was taken by using questionnaire. Meanwhile, data analysis methodology of students’ learning activity, students’ learning result and students’ response are descriptive quantitative method. The data of learning activity was collected by using observation sheet, the data of students’ learning result collected by tasks and test evaluation, and students’ response collected by using questionnaire. The result of this research shous: 1) students learning activity result improved, which can be seen from the average score of learning activity in cycle I, it is 12.50, it categorized active and in cycle I, it is 19.27 it categorized very active: 2) the average score of classroom improved from 71.45 in cycle I become 84.28 in cycle II, it qualification exhaustive and the percentage improved from cycle I into cycle II, it is 12.83%, and classical exhaustive  improved from cycle I, it is 38.46% to 88.46% in cycle II: 3) students’ response in implementation of PQRST method in TIK subject especially in competency standard comprehending the uses of technology information and communication were positive with average score 47.